The Implementation Of Public Service Principles In Birth Certificate Making (Perspective of Transparency and Accountability Study at Civil Registry Office of Trenggalek Regency) - Widya Santy Ratrinirmala (Jurnal Administrasi Publik, 2016)
Abstract: The Implementation of Public Service Principles in Birth Certificate Making (Perspective of Transparency and Accountability Study at Civil Registry Office of Trenggalek Regency). The Official of Demographic and Civil Registration in Trenggalek Regency was the provider of public service, and one public service assigned to be served was birth certificate administration. Transparency principle was applied to birth certificate administartion through three aspects such as the openness of service delivery, the easiness of information access, and the reliable mechanism of service delivery procedure. The application of accountability principle to birth certificate administration was considering five aspects such as fast and proper information delivery to the community, officer responsibility, community participation, and available structure to assess officer performance.Result of research indicated that the implementation of transparency and accountability principles in birth certificate administartion at the Civil Registry Ofiice of Trenggalek Regency had suffered from problems such as less precision of service timing, lack of community awareness, less reliable structure-infrastructure, and limited number of employee. Therefore, the implementation of public service principles, including transparency and accountability, should be improved at the Civil Registry Office of Trenggalek Regency. Keywords: public services, birth certificate, transparency principles, accountability principles Abstrak: Pelaksanaan Asas Pelayanan Publik dalam Pembuatan Akta Kelahiran (Perspektif Transparansi dan Akuntabilitas Studi di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Trenggalek). Dinas Kependudukan dan Pencatatan Sipil Kabupaten Trenggalek merupakan penyelenggara pelayanan publik salah satunya dalam pembuatan Akta Kelahiran. Pelaksanaan asas transparansi dalam pembuatan Akta Kelahiran dilihat dari tiga aspek yaitu keterbukaan proses penyelenggara pelayanan, kemudahan untuk memperoleh informasi, dan mekanisme prosedur pelayanan Kemudian, dalam pelaksanaan asas akuntabilitas dilihat dari lima aspek yaitu penyajian informasi secara cepat dan tepat kepada masyarakat, kemampuan petugas, tanggungjawab petugas, partisipasi masyarakat, dan sarana untuk menilai kinerja petugas. Berdasarkan hasil penelitian yang dilakukan penulis pelaksanaan asas transparansi dan akuntabilitas dalam pembuatan Akta Kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Trenggalek mengalami berbagai permasalahan, seperti kurangnya ketepatan waktu pelayanan, kurangnya kesadaran masyarakat, sarana prasarana kurang memadai, dan keterbatasan jumlah pegawai. Oleh sebab itu, diperlukan adanya peningkatan pelaksanaan asas transparansi dan asas akuntabilitas pelayanan publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Trenggalek. Kata Kunci: pelayanan publik, akta kelahiran, asas transparansi, asas akuntabilitas